Assistance for People with HIV/AIDS in Enhancing Emotional Regulation Through the Utilization of Bibilotherapy at KPA Bandung City - Anggriyana Tri Widianti; Eli Lusiani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
According to the World Health Organization (WHO), the prevalence of HIV/AIDS is rising in all age groups. Members of KPA Bandung City who have HIV/AIDS (PLWHA) have psychological issues. PLWHA's main problems include feeling sad and angry with God, frequently crying, and believing they are dying (feeling depressed). The psychological consequences of HIV/AIDS can have an impact on the survival of HIV-positive adolescents. As a result, it is critical to recognize and treat these psychological symptoms, one of which is the use of emotion regulation strategies.People suffering from chronic illnesses, which are sometimes fatal, rely on their faith and religious practices to find support and acceptance for their suffering. As a result, more attention must be paid to the management of emotion regulation. Cognitive-behavioral therapy (CBT) can help adolescents with HIV/AIDS improve their emotional regulation strategies and religious coping. Through bibliotherapy, the Youth Empowerment Program with HIV/AIDS aimed to improve the emotional regulation. This community service activity is conducted by assisting PLWHA youth through the use of bibliotherapy. Activities for up to 5 PLWHA will be carried out at the KPA office. Community service is performed by asking PLWHA to read a book on the topic of PLWHA once. Furthermore, bibliotherapy is given to PLWHA for one session by asking them to read a book with the theme of becoming successful HIV AID patients. People living with HIV are able to capture the meaning of every event that occurs in the reading during the stages after reading. There was a change in the regulation of PLHA's emotions after being given bibliotherapy, namely being positive.